Systematizing an Expanded Lumbar Interlaminar Endoscopic Approach: The 10 Steps of Castro-Brock for Increased Security - Castro, João Paulo Souza; Cordenonssi, Julianne Tannous; Brock, Roger Schmidt (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Introduction With increasing life expectancy, there is a rising incidence of degenerative spinal pathologies, particularly in the elderly population. Minimally invasive techniques are becoming increasingly attractive due to the higher prevalence of comorbidities in older patients. Endoscopic spine surgery offers advantages such as early rehabilitation, reduced postoperative pain, minimized muscle damage, and shorter hospital stays.Objectives To enhance the safety of the interlaminar approach and minimize complications, we propose the systematic application of an expanded interlaminar technique, termed the “Castro-Brock technique.” Direct visualization of accurate anatomy is emphasized for successful endoscopic navigation.Methods The Castro-Brock technique is described in a step-by-step manner, comprising 10 steps with illustrative images. The technique involves an initial puncture on the upper lamina, identification of bony structures, drilling and enlarging the interlaminar bone window, en bloc flavectomy, and precise identification of the descending root before accessing the disc.Results The Castro-Brock technique facilitates improved visualization of anatomy and provides decompression of neurological structures before disc access. This systematic approach reduces the risk of inadvertent neurological injury and other surgical complications associated with interlaminar access.Conclusions The Castro-Brock technique represents a valuable addition to the armamentarium of lumbar endoscopic spine surgery. Ensuring meticulous anatomical visualization and pre-disc decompression of neural structures enhances surgical safety and optimizes patient outcomes.
Keywords: endoscopic spine surgery; interlaminas approach; minimally invasive